How to make life unlivable in a neighborhood: the utilization of mobbing in urban renewal negotiations - Tiryaki, Tugba Tuncer; Dincer, Iclal (SPRINGER, 2026)
The concept of mobbing in the urban renewal process offers a unique lens through which to understand dynamics apart from conventional depictions of the negotiation phase. This study, which focuses on two distinct urban renewal negotiation phases in Istanbul, one private-led phase and one state-led phase, aims to conceptualize, through this lens, the psychological pressures experienced by residents who refuse to accept a compensation plan. The process of mobbing is rooted in generating consent by creating conditions that render the neighborhood uninhabitable. This is accomplished through various mobbing actions that involve actors such as neighbors, family members, developers, and the state and target anything from residents' social relationships to their built environment. Through these actions, they weaken residents' attachment to their homes and communities while also fostering division and distrust among neighbors. Mobbing operates as a strategic mechanism to produce consent, which blurs the lines between voluntary and coerced agreement. In the context of urban renewal, mobbing also highlights the social costs of the process, including psychological or social distress, social disempowerment, and the erosion of neighborhood cohesion. Thus, projects which promise an improved life through urban renewal, paradoxically, negatively impact daily life even before they begin. Given the widespread role of urban renewal in shaping urbanization, particularly in T & uuml;rkiye and similar contexts, addressing the mobbing process and its psychological and social implications is imperative.
Keywords: Urban renewal; Negotiation phase; Mobbing; Bullying; Violence; DISPLACEMENT; GENTRIFICATION; DISORDER; POLITICS; WORK; CITY; REGENERATION; HARASSMENT; ISTANBUL; Environmental Sciences & Ecology; Public Administration; Urban Studies